2018
DOI: 10.1111/odi.12916
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus non‐surgical treatment of actinic cheilitis: A systematic review and meta‐analysis

Abstract: In this systematic review, the surgical treatment was more favorable than non-surgical for AC. Meanwhile, further studies are needed that should maximize methodological standardization and have greater rigor of the data collection process. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 45 publications
0
29
0
3
Order By: Relevance
“…A broad variety of therapeutic measures are available for AC including cryotherapy, electrodesiccation, carbon dioxide or Er:YAG laser ablation, trichloroacetic acid chemical peel, surgical excision (vermilionectomy), 5-fluorouracil, imiquimod, ingenol mebutate, diclofenac 3% gel with hyaluronic acid 2.5% and photodynamic therapy. 3,6 A recent review analysed the outcome of surgical (n = 122) vs. non-surgical (n = 161) treatments in 283 patients with AC who were included in 10 studies. Remission and recurrence rates were 92.8% and 8.4% in patients who received surgical treatment and 65.9% and 19.2% in patients who received non-surgical interventions, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A broad variety of therapeutic measures are available for AC including cryotherapy, electrodesiccation, carbon dioxide or Er:YAG laser ablation, trichloroacetic acid chemical peel, surgical excision (vermilionectomy), 5-fluorouracil, imiquimod, ingenol mebutate, diclofenac 3% gel with hyaluronic acid 2.5% and photodynamic therapy. 3,6 A recent review analysed the outcome of surgical (n = 122) vs. non-surgical (n = 161) treatments in 283 patients with AC who were included in 10 studies. Remission and recurrence rates were 92.8% and 8.4% in patients who received surgical treatment and 65.9% and 19.2% in patients who received non-surgical interventions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Remission and recurrence rates were 92.8% and 8.4% in patients who received surgical treatment and 65.9% and 19.2% in patients who received non-surgical interventions, respectively. 3 However, these findings were challenged due to the small number of included patients, lacking assessment of bias risk and the fact that all but one study had a low level of evidence. 12 In conventional PDT, the topical photosensitizer (5-aminolevulinic acid or methyl aminolevulinate) is applied under an occlusive foil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-surgical approach is less invasive and has fewer secondary effects. But contrarily, in a systematic review by Carvalho et al [34], the surgical treatment was found to be more favorable than non-surgical for AC. However, it is very important to protect lips from sunlight.…”
Section: Actinic Chellitismentioning
confidence: 91%
“…Surgery treatment options include cryosurgery, electrosurgery, laser vaporization and scalpel vermilionectomy. In a systematic review conducted by Vasconcelos Carvalho et al remission rate and recurrence rate of actinic cheilitis were higher and lower respectively for surgical treatment compared to non surgical treatment [6]. Cheilitis granulomatosa (of Miescher) is a rare, painless and idiophatic swelling of the lip belonging to the larger group of orofacial granulomatosis caused by non-caseating granulomatous inflammation.…”
mentioning
confidence: 99%